Piety as social capital: masculinity, moral policing, and Islamic religious education in a vocational high school - M Renaldy Fadillah (UIN Salatiga, 2026)
This study examines how male identity and piety are constructed within school culture through Islamic Religious Education (IRE) at SMK Doa Bangsa Palabuhanratu. It explores how the “ideal male” is shaped in daily school life, how piety is negotiated within peer relationships, and how IRE may both redirect and reinforce certain forms of masculinity. Employing a qualitative approach, the research involved 18 participants, including IRE teachers, homeroom or student affairs staff, and male students from grades X–XII. Data were collected between January and February 2026 through classroom observations, semi-structured interviews, and document analysis. Thematic analysis focused on masculinity as a performative and relational practice, piety as social capital, and IRE as a mediating space for moral formation. The findings reveal that male identity is shaped through continuous negotiation between toughness, vocational discipline, peer recognition, and religious values. Piety functions both as a moral ethic that strengthens responsibility and adab and as a status marker that may encourage moral policing. Teacher role modelling and consistent school norms play an important role in fostering ethical and collaborative masculinities.